Impact Of Conflict Management On a Nigerian Public Sector Organization: The Performance Of Specific Employees in Kogi State. - Abalaka, J.N; Ajiteru, S.A.R; Sulaiman, T.H (Digital Innovation : International Journal of Management, 2025)
This study looked into how employees' performance in a Kogi State public sector organization was affected by conflict management. The survey research design was used in this investigation. There were 100 responders in all were chosen for the study by the use of stratified sampling. A survey was employed to gather primary data. Descriptive statistics were used to assess the acquired data. Regression analysis and the correlation coefficient were used to examine the hypotheses. The results showed that an organization's conflict management system affects employee performance inside the company and that successful conflict management improves employee performance within the organization. In order to foster a positive work environment and ensure that there is effective communication between all employee categories within the organization, it was suggested that the organization start training and retraining its staff in conflict management. As a result, there will be less conflicts within the company.